2019
DOI: 10.1002/mrd.23280
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 treatment regulates apoptosis, antioxidant defense system, and DNA integrity in the epididymal sperm of an aged rat model

Abstract: The present study aimed to investigate the effects of vitamin D3 in the epididymal sperm cells of D‐gal‐induced aged rats. It is well known that during aging sperm quality and quantity declines and leads to age‐related infertility problems in males. The results of the present study showed that there were elevated levels of oxidative stress and poor DNA integrity of sperm of aged rats. The expression of BCL2 also showed a significant decline in the sperm of aged rats, however, the expression of BAX and active c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…As well, here, our results showed that d ‐gal increased MDA levels and decreased SOD and GPx activity in the heart and brain. Concerning vitamin D, Jeremy et al ( 2019 ) showed that it can delay testicular aging through the decrease in oxidative stress and the improvement of cellular antioxidant defense. In agreement, the present work shows that the two regimens of a low dose of vitamin D could decrease MDA levels and increase SOD and GPx activity, thus preventing and counteracting d ‐gal‐induced effects.…”
Section: Discussionmentioning
confidence: 99%
“…As well, here, our results showed that d ‐gal increased MDA levels and decreased SOD and GPx activity in the heart and brain. Concerning vitamin D, Jeremy et al ( 2019 ) showed that it can delay testicular aging through the decrease in oxidative stress and the improvement of cellular antioxidant defense. In agreement, the present work shows that the two regimens of a low dose of vitamin D could decrease MDA levels and increase SOD and GPx activity, thus preventing and counteracting d ‐gal‐induced effects.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of 1α,25(OH) 2 D 3 on reproductive health has been elucidated 42 . Jeremy et al reported that 1α,25(OH) 2 D 3 can significantly improve the decline of male reproductive system function in aging rats through anti‐oxidation, reducing apoptosis, improving DNA integrity and spermatogenesis 43,44 . In addition, in diabetic rats, 1α,25(OH) 2 D 3 showed a certain protective effect on testicular function through suppressing inflammation and inhibiting cell apoptosis 45 .…”
Section: Discussionmentioning
confidence: 99%
“…VD induces an overall pro-survival transcriptional program characterized by upregulated expression of anti-apoptotic genes and downregulated expression of pro-apoptotic genes [ 142 ]; in addition, VD determines the non-genomic activation of the PI3K-Akt survival kinase pathway [ 143 ], it also reduces apoptosis of EC by increasing NO production (see above) .…”
Section: Vitamin D In Diabetic Retinopathymentioning
confidence: 99%